2019
DOI: 10.1158/0008-5472.can-18-2156
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Heme Synthesis and Uptake Underpin Intensified Oxidative Metabolism and Tumorigenic Functions in Non–Small Cell Lung Cancer Cells

Abstract: HSP2HSP2 HEME HCP1 HRG1 HEME HEME HEME CYT NUC ER ALA SLung cancer cells exhibit elevated heme synthesis and uptake, which promotes tumorigenic functions. Heme-sequestering peptide 2 (HSP2) inhibits heme uptake and suppresses tumor growth. V [ ] Lung tumors Non-small cell lung cancer cell Normal lung I II III IV ATP ADPTumors of human non-small cell lung cancer (NSCLC) are heterogeneous but exhibit elevated glycolysis and glucose oxidation relative to benign lung tissues. Heme is a central molecule for oxidati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 56 publications
2
94
0
Order By: Relevance
“…Apart from ECs, nonsmall cell lung carcinoma cells with elevated heme synthesis levels had increases in enzyme activities of the ETC. Increased production of heme was associated with increased migratory and invasive properties of these cells and xenograft tumors in mice (Sohoni et al, 2019). Here, we demonstrated how heme depletion by blockade of the terminal synthesis enzyme FECH led to defects in COX IV and ETC disruption ( Figure 7).…”
Section: Discussionmentioning
confidence: 60%
“…Apart from ECs, nonsmall cell lung carcinoma cells with elevated heme synthesis levels had increases in enzyme activities of the ETC. Increased production of heme was associated with increased migratory and invasive properties of these cells and xenograft tumors in mice (Sohoni et al, 2019). Here, we demonstrated how heme depletion by blockade of the terminal synthesis enzyme FECH led to defects in COX IV and ETC disruption ( Figure 7).…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, a study performed in human patients in order to analyze metabolic pathways’ flow in non-small-cell lung cancer (NSCLC) displayed that high rates of both glycolysis and oxidative metabolism can be observed in this cancer type, highlighting a metabolic heterogeneity strongly influenced by microenvironment. In addition, Sohoni et al highlighted that the elevated OXPHOS activity and tumorigenicity characterizing NSCLC cells are related to elevated both flux and function of heme, a key molecule in mitochondrial OXPHOS [ 26 ].…”
Section: Targeting Mitochondrial Metabolism In Cancermentioning
confidence: 99%
“…Several studies have correlated a high heme dietary intake through the consumption of red and processed meat with the pathogenesis of different carcinomas, such as esophageal, gastric, colorectal, breast, endometrial, pancreatic, and lung cancer. In addition, increased heme biosynthesis and uptake have been found in several tumors, including non-small-cell lung cancer, in which high heme levels, as well as an increased activity of heme proteins, have been shown to underlie metabolic rewiring and tumor progression [ 26 , 78 , 79 ]. This evidence highlights the important role in cancer of heme uptake, as well as of its biosynthesis and incorporation into oxygen-utilizing heme proteins, and has led to the study of molecules targeting these processes as a new anticancer strategy [ 80 ] ( Figure 3 ).…”
Section: Targeting Mitochondrial Metabolism In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Heme directly binds to and modulates the activities of certain cellular proteins, such as the yeast heme-regulatory protein Hap1 [51,52] and the mammalian nuclear receptor Rev-erbα [49,53]. Experimental studies have increasingly shown that heme is a central signaling molecule in an array of physiological and pathological processes, including neurodegeneration, tumorigenesis, and adipogenesis [54][55][56].…”
Section: Introductionmentioning
confidence: 99%